PERGERAKAN PENDUDUK KOTA DEPOK MENUJU KE TEMPAT BEKERJA TAHUN 2001 - Sitanala, Frans (UI Scholars Hub, 2023)
Depok’s Resident Movement to Their Workplace in 2001. The data of commuters from Depok town were taken from six Depok’s subdistricts to get the information of their work location, their transportation and the interaction between Depok town with DKI Jakarta, Bogor, Tangerang, Bekasi regions (Botabek). The results show that majority the commuters went to DKI Jakarta as their workplace which was dominant in all subsdistrics. The commuters dominantly used non-train public transports. The strong interaction were happened between Depok town and South Jakarta and East Jakarta, the weak one was happened between Depok town with Tangerang